Interactive Communicative Teaching and the Young Indian Learner - Gupta Deepti (Universidad Nacional de Colombia, 2004)
In classrooms where English is not the mother tongue and where age-old teaching methodology rules the roost, it is not easy to make changes, especially radical ones. This case study shows how these reforms can be self-defeating if they are imposed without an attempt at a gradual, gentle and well thought out implementation. This is a slightly modified and revised version of a paper presented at the "Language in the Mind" International conference organized by the Singapore University, Singapore in September 2000. Key words: Communicative, Task-based, Interactive, Learner-centered, Structural, Lecture-based, Pedagogy En las clases en las que el inglés no es la lengua materna y en las que predomina una metodología anticuada de enseñanza, no es fácil efectuar cambios, especialmente cambios radicales. Este caso demuestra cómo estas reformas pueden fracasar si se las impone repentinamente sin una implementación gradual y bien planificada. Esta es una versión modificada y revisada de un documento presentado en la conferencia internacional "Idioma en la mente" organizada por la Universidad de Singapore en Singapore en septiembre de 2000. Palabras claves: Enseñanza-Lenguas Extranjeras, Enfoque Comunicativo, Enfoque basado en Tareas, Enfoque Interactivo, Enfoque centrado en el Estudiante, Enfoque Estructural